PENGEMBANGAN SIPS ARCHIVING (SMART INTELLIGENT PROCESSING SYSTEM) SEBAGAI SISTEM DIGITAL PENGARSIPAN FAKTUR UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN DOKUMEN DI RSABL - Yogi Catur Putra; Maya Aprilianingsih; Elvina Dwi Saputri; Tyas Nurul Mudaminah; Darya Aisya Candra (Journal of Hospital Administration and Excellent Health Service, 2026)
Introduction: Conventional invoice archiving in hospitals often faces bottlenecks such as delayed document retrieval, risks of physical damage, and financial workflow inefficiencies. This study aims to develop SIPS Archiving (Smart Intelligent Processing System) as a digital invoice management solution at RSABL. Method: This study utilized a Research and Development (R&D) design with the FAST (Framework for the Application of System Thinking) system development model. Data were gathered through document workflow observations, in-depth interviews with finance staff, and system usability testing using the System Usability Scale (SUS) questionnaire at RSABL. Result: The implementation of SIPS Archiving successfully digitized 100% of incoming invoices using OCR (Optical Character Recognition) automatic data extraction. Document search times significantly improved from an average of 15 minutes to under 5 seconds, and the SUS score reached 82.4, falling into the "excellent" usability category. Conclusion: The development of SIPS Archiving is proven to be highly effective in improving the management efficiency, security, and accessibility of invoice documents at RSABL. Keyword: sips archiving, invoice digitization, document efficiency, hospital administration